(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Digital technologies are booming worldwide in all the sectors including the banking industry. In order to sustain in the highly competitive world, banks introduced electronic banking (E-banking) to sustain and maximize the profit of the business. From this point of view, customer satisfaction had become an important component to ensure the survival of the business. Electronic Banking use of computers and telecommunication to enable banking transaction to be done by telephone or computer rather than through human inter action. It features include electronic funds transfers for retail purchases, Automated Teller Machine (ATM) and automatic payroll deposits andBill payments. Some banks offers home banking were by a person with a personal computer can make transactions either, via a direct connection or by accessing a website, E-Banking has vastly reduced the physical transfer of paper money coinage from one place to another on even from one person to another. This paper intends to understand the Customer Satisfaction of E-Banking Services in Indian Bank. The study has been made by conducting a survey in Kanniyakumari District of Tamil Nadu State. For that, the researcher collected 60 samples from the respondents and percentage, Garret ranking method and Chi- squre test used for this study